Management of saccular superior cerebellar artery aneurysms: The Buffalo experience case series and systematic review. Issue 2 (April 2023) - Lim, Jaims; Nyabuto, Elizabeth; Aguirre, Alexander O; Waqas, Muhammed; Vakharia, Kunal; Cappuzzo, Justin M; Siddiqui, Adnan H
Background: Results of the management of superior cerebellar artery (SCA) aneurysms are typically reported in combination with those for all posterior circulation aneurysms. We report our experience with the management of SCA aneurysms and a systematic review of the endovascular management of these rare aneurysms. Methods: Patients with saccular SCA aneurysms that were not associated with arteriovenous malformations and who presented to our institute between 2000 and 2017 were identified. Patient demographics, aneurysm characteristics, interventions, and follow-up data were collected, compared, and analyzed. For the review, data including number of aneurysm treated, outcomes, follow-up, and occlusion rates were collected. Results: Mean age of the 31 identified patients was 57.4 ± 12.3 years; 19.4% were men. Mean aneurysm size was 5.1 ± 2.9 mm. Seven of 21 patients with unruptured aneurysms were managed conservatively. Ten patients (32.3%) presented with ruptured aneurysms (mean aneurysm size, 6.2 ± 3.2 mm). Treatment was successfully completed in 22 patients: 13-primary coiling, 7-stent-assisted coiling, and 2-microsurgical clipping. Complete angiographic aneurysm occlusion after primary treatments was achieved in 19 (86.4%) patients. The total complication rate among treated patients was 4.2% (1 of 24 treated aneurysms). No minor complications occurred. However, in 2 patients, coil embolization was attempted but aborted due to coil protrusion into the parent artery. Clinical and angiographic follow-up data were available for 26 observed or treated patients. Mean follow-up duration was 5.3 ± 4.5 years. Six articles met our review inclusion criteria and demonstrated similar mean treated aneurysm sizes ranging from 4.6–7.7 mm, and follow-up from these articles ranged from 15.3–50 months. Conclusions: Endovascularly treated patients with ruptured and unruptured SCA aneurysms, of which most were <7 mm, had good clinical outcomes with minimal complications.